The use of ict (information and communication technology) in the study of natural sciences by masters of higher educational institutions - Hladun, T. (Journal of Education, Health and Sport, 2020)
One of the leading tendencies in the development of contemporary education is the informatization of society. The informatization process requires a constant improvement of the professional level of both an individual and a team, encourages being able to work with information and communication devices, requires further training of masters of natural sciences, new content and quality of education. It is important to have a system where the sections of natural sciences, ICT, areas of technological progress and various issues of applied biology, chemistry and physics are interconnected. It is STEM education that can be used as such a system. This article is dedicated to using ICT at the classes of natural sciences at higher educational institutions. The main problems on the way to the implementation of STEM education have been analyzed.